2017
DOI: 10.3390/cli5030074
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Past and Mid-Century Rainfall Indices over the Ouémé River Basin, Benin (West Africa)

Abstract: This study analyzed the trends of extreme daily rainfall indices over the Ouémé basin using the observed data from 1950 to 2014 and the projected rainfall of regional climate model REMO (REgional MOdel) for the period 2015-2050. For future trends analysis, two Intergovernmental Panel on Climate Change (IPCC) new scenarios are considered, namely RCP4.5 and RCP8.5. The indices considered are number of heavy rainfall days, number of very heavy rainfall days, consecutive dry days, consecutive wet days, daily maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…The statistically significant decreasing trends in rainfall and runoff observed shows that the basin had not recovered from the drought, although the current annual rainfall and runoff is not as high as it was in the 1950s. This trend of decrease had been projected to continue to mid-century based on a study conducted at an adjacent catchment [12].The higher recent high runoff pattern at Kompongou station was due to unsustainable land-use management and rapid population growth leading to a process called the 'Sahelian Paradox' [24]. The Sahelian paradox is an observed runoff increase despite low rainfall.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The statistically significant decreasing trends in rainfall and runoff observed shows that the basin had not recovered from the drought, although the current annual rainfall and runoff is not as high as it was in the 1950s. This trend of decrease had been projected to continue to mid-century based on a study conducted at an adjacent catchment [12].The higher recent high runoff pattern at Kompongou station was due to unsustainable land-use management and rapid population growth leading to a process called the 'Sahelian Paradox' [24]. The Sahelian paradox is an observed runoff increase despite low rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…The Mann-Kendall test evaluates the relative magnitudes of data and is widely used in hydrology [12,19].The advantage of this test is that the data need not comply with any particular distribution. The data values are assessed as an ordered time series.…”
Section: Trend Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies [3] [4] [5] show that impacts of climate extremes are mostly depending on the spatial scale considered and vary from a region to another, from country to country and even from one local area to another within the same country. For Africa, many previous studies have investigated extreme events and have showed that changes in extreme temperature and precipitation are contrasting [6] [7] [8].…”
Section: Introductionmentioning
confidence: 99%